ANALISIS MINIMALISASI LIMBAH PADAT DOMESTIK DENGAN PENERAPAN PROGRAM GREEN WAREHOUSE DAN OFFICE - Nur hayari (JURNAL TECHLINK, 2023)
The research in this thesis is motivated by the large amount of domestic solid waste at PT. X, especially in the warehouse and office areas, there is also some solid waste at PT. X has not been managed effectively is the reason PT. X implements green house and office programs as an effort to minimize existing domestic solid waste. The formulation of the problem in this study is how the effect of implementing green warehouse and office programs in minimizing domestic solid waste (garbage). While the purpose of this study is to determine the application of the werehouse and office programs to minimize domestic solid waste (garbage generation) and to find out the responses of employees and janitors regarding green warehouse and office program activities in minimizing domestic solid waste (garbage) at PT. X.The research approach used in this study is a quantitative and qualitative approach. Data collection techniques using primary data and secondary data. While the population used is all solid waste generated in the warehouse area and office space of PT. X every day then in taking samples using stratified sample techniques and simple random sampling. The results of the study show that the application of minimization of domestic solid waste (garbage generation) is carried out by PT. X with green warehouse and office programs starting from different containers with the provisions of SNI 19-3983-1995, solid waste collection is carried out routinely, namely in the afternoon, solid waste transfers from 15.00 to 17.00 and solid waste treatment is disposed of to the area. Area by carrying out waste bank activities. The application of domestic solid waste minimization at PT. X is already running but not in accordance with existing regulations. Green warehouse and office programs in the minimization of domestic solid waste (garbage) starting from storage in the office space area according to employees and cleaning staff produce organic solid waste and paper. In the office space area, which is in room 2 by 40%, in room 3 by 20% and in room 4 by 60%, while in the warehouse area, which is in the admin room by 20%, the relocation has been implemented well by the cleaners.